Nepal’s Rapid Rural Electrification Achievement: A Review - Basnet, Suman (Kathmandu University Journal of Science, Engineering and Technology, 2024)
Nepal has been able to accelerate electricity access to rural areas very rapidly from early 2000s. Though the existing literature provides insights into the factors, enablers, challenges, and institutional models influencing rural electrification in Nepal, there is currently very little assessment of the specific factors that led to Nepal’s rapid rural electricity access in the first two decades of this century. This review paper investigates what spurred this rapid rural electrification in Nepal. The study employs a literature review approach and uses the multi-level perspective and energy justice frameworks for a holistic interpretation of findings of the literature review. Analysis of the findings from the literature review indicate that Nepal’s rapid electrification can be assessed primarily through the perspectives of governance and policies. The discussion also touches on the institutional context, the politics surrounding the electrification transition, and policy innovations. The effectiveness of the polices is also analysed through an energy justice perspective. The analysis highlights challenges and disparities in geographical distribution and energy justice. The paper argues that Nepal’s rural electricity access was boosted by political and socio-economic conditions, like advent of democracy and large-scale foreign employment, and was propelled by innovative government policies for grid based and off-grid rural electrification. However, it also concludes that work still needs to be done from an energy justice perspective to bring about geographical and economic equity in the effort.